2014
DOI: 10.1111/anec.12146
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Tissue Perfusion Predicts the Evolution of Fragmented QRS in Patients with ST‐Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: Our findings showed that despite complete ST-segment resolution in all patients, fQRS is independently associated with impaired microvascular myocardial perfusion. So, fQRS, as a simple and easily available noninvasive marker, may be useful in stratification of high-risk patients with increased extent of infarcted myocardium who underwent primary PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Imperfect ST-segment resolution after PCI was independently associated with cardiac dysfunction, cardiac death, and short- and long-term clinical prognosis in patients with STEMI 21 . Recent studies have negatively correlated fQRS with reperfusion parameters such as ΣSTR12, 13 and myocardial blush grade 11 in patients with STEMI. Similarly, we have found that new onset or persistent fQRS was significantly associated with impaired myocardial reperfusion as estimated by ΣSTR after PCI in our cohort.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Imperfect ST-segment resolution after PCI was independently associated with cardiac dysfunction, cardiac death, and short- and long-term clinical prognosis in patients with STEMI 21 . Recent studies have negatively correlated fQRS with reperfusion parameters such as ΣSTR12, 13 and myocardial blush grade 11 in patients with STEMI. Similarly, we have found that new onset or persistent fQRS was significantly associated with impaired myocardial reperfusion as estimated by ΣSTR after PCI in our cohort.…”
Section: Discussionmentioning
confidence: 98%
“…In patients with STEMI, prolonged QRS time was associated with increased long-term mortality due to increased incidence of heart failure, arrhythmia, and ischemia 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. In our study, fQRS was related to prolonged QRS duration after PCI (p < 0.001) with lesser delta QRS time ( p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] In a recent study, Lorgis et al 5 showed that the presence of fQRS was associated with a significantly lower left ventricular ejection fraction, increased left ventricular volumes, a larger infarct size, and a larger peri-infarct zone in patients who underwent cardiac magnetic resonance imaging during the week after acute myocardial infarction. [2][3][4][5] In a recent study, Lorgis et al 5 showed that the presence of fQRS was associated with a significantly lower left ventricular ejection fraction, increased left ventricular volumes, a larger infarct size, and a larger peri-infarct zone in patients who underwent cardiac magnetic resonance imaging during the week after acute myocardial infarction.…”
Section: Dear Editormentioning
confidence: 99%
“…The presence of a fragmented QRS (fQRS) complex including narrow or wide QRS complex, which corresponds to the depolarization of the right and left ventricles of the human heart is frequently recorded following surface electrocardiograms (ECGs). Previous studies have identified that fQRS complex on surface ECG is a predictor of adverse cardiovascular events, including cardiac mortality and heart failure ( 3 , 4 ). In clinical terms, the presence of fQRS is common among patients with biventricular enlargement and myocardial infarction (MI) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%